Effectiveness of teachers training in BRAC schools - Sultan, Sania; Khan, Md. Kaisar Ali; Imam, Syeda Rumnaz (BRAC Research and Evaluation Division (RED), 2020)
The study attempted to evaluate the newly designed training module for teachers who are teaching English in class three, four, and five of BRAC NFPE schools. With the knowledge of BRAC graduates' relative weakness in English when they join the Government Formal Schools, the Materials Development Unit (MDU) has made a concerted effort in addressing this issue concerning English teaching. Also, MDU's goal entailed a plan to break away from the top down model of training, traditionally followed. The study aimed to see how much of these goals have been met, what are the problems involved, and how to address those. A teachers guide has been developed based on the Class III Textbook, which delineates six steps in teaching English. The guide provides step by step instruction in teaching English. The study was undertaken at the initial stage of the training process. MDU has been selecting and training a group of Master Trainers. The Master Trainers then have been training the field staff, and finally the field staff have been providing the same to the teachers through the monthly refreshers. Since the training schedule involved several stages, the most important issue was to find out how much of the dissemination has been happening in a standardized way, and the impact of training on the trainees, particularly the teachers, who are the gatekeepers of successful implementation. The impact of training can be generally located in two domains, i.e., cognitive and affective. Training helps to improve the knowledge base of a subject, and also the trainees do have an emotional response towards the training. The study attempted to explore both the domains. By using a variety of instruments like opinion questionnaires, group discussions, observations, and tests, the researchers tried to derive the impact of this training on all concerned, particularly the teachers, who are the final recipients and gatekeepers of successful implementation.